Lacticaseibacillus rhamnosus Fmb14 ameliorates hyperuricemia-induced hepatocyte pyroptosis via NLRP3 inflammasome cascade inhibition - Hongyuan Zhao; Xiaoyu Chen; Li Zhang; Fanqiang Meng; Libang Zhou; Zhaoxin Lu; Yingjian Lu (Food Science and Human Wellness)
Hyperuricemia is a high-risk factor for the development of gout and renal fibrosis, but the adverse effects of hyperuricemia on the liver have been seriously neglected. This research investigated the ameliorating effect of Lacticaseibacillus rhamnosus Fmb14 on hyperuricemia induced liver dysfunction both in vitro and in vivo. Cell free extracts of high dose L. rhamnosus Fmb14 treatment reduced the death rate of HepG2 cell lines from 24.1% to 14.9% by inhibiting NLRP3 recruitment, which was mainly activated by reactive oxygen species release and mitochondrial membrane potential disorder. In purine dietary induced hyperuricemia (PDIH) mice model, liver oedema and pyroptosis were ameliorated after L. rhamnosus Fmb14 administration through downregulating the expression levels of NLRP3, caspase-1 and gasdermin-D from 1.61 to 0.86, 3.15 to 1.01 and 5.63 to 2.02, respectively. L. rhamnosus Fmb14 administration restored mitochondrial inner membrane protein (MPV17) and connexin 43 from 2.83 and 0.73 to 0.80 and 0.98 respectively in PDIH mice, indicating that dysbiosis of mitochondrial membrane potential was restored in liver. Intriguingly, PDIH pyroptosis stimulates the process of apoptosis, which leads to severe leakage of hepatocytes, and both of pyroptosis and apoptosis were decreased after L. rhamnosus Fmb14 treatment. Therefore, L. rhamnosus Fmb14 is a promising biological resource to maintain homeostasis of the liver in hyperuricemia and the prevention of subsequent complications.